Literatura de Testemunho e a denúncia de uma voz ausente em Primo Levi e Bernardo Kucins - Friedman, Iris (2016)
This dissertation proposes a study of the works É isto um homem? (1988), by Primo Levi, and K.- Relato de uma busca (2014), by Bernardo Kucinski, utilizing an approach from the Testimony Literature. Prioritizing this literary category to conduct a Reading – that employs fictional elements to cope with texts of witnessing nature – benefits the understanding of limit-events such as the Shoah and the Brazil´s military dictatorship, which belong to the Era of Catastrophes. The analysis of tensions between the presence and absence in the representations of the trauma highlights the issue of negative power as a way to re-dimension the work according to its narrative possibilities